Welcome to Westonci.ca, the Q&A platform where your questions are met with detailed answers from experienced experts. Our platform offers a seamless experience for finding reliable answers from a network of experienced professionals. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
Let's solve this step-by-step:
We start with the given equation:
[tex]\[ 148 = 2(6w + 6h + hw) \][/tex]
First, distribute the 2 on the right-hand side:
[tex]\[ 148 = 12w + 12h + 2hw \][/tex]
We want to solve for [tex]\( w \)[/tex] in terms of [tex]\( h \)[/tex]. To do this, let's isolate [tex]\( w \)[/tex]:
1. Combine like terms on the right-hand side:
[tex]\[ 148 = 12w + 12h + 2hw \][/tex]
2. Move the [tex]\( 12h \)[/tex] term to the left-hand side:
[tex]\[ 148 - 12h = 12w + 2hw \][/tex]
3. Factor [tex]\( w \)[/tex] out of the terms on the right-hand side:
[tex]\[ 148 - 12h = w(12 + 2h) \][/tex]
4. Divide both sides by [tex]\( (12 + 2h) \)[/tex] to isolate [tex]\( w \)[/tex]:
[tex]\[ w = \frac{148 - 12h}{12 + 2h} \][/tex]
Let's compare this to the given equivalent equations:
- [tex]\( w = \frac{148 - 6h}{12 + h} \)[/tex]
- [tex]\( w = \frac{148 - 12h}{12 + 2h} \)[/tex]
- [tex]\( w = 136 - 14h \)[/tex]
- [tex]\( w = 136 - 10h \)[/tex]
Comparing directly, we see that:
[tex]\[ w = \frac{148 - 12h}{12 + 2h} \][/tex]
is exactly equivalent to our derived equation because both the numerator and denominator match.
Thus, the equivalent equation is:
[tex]\[ w = \frac{148 - 12h}{12 + 2h} \][/tex]
So, the correct equation is:
[tex]\[ w = \frac{148 - 12h}{12 + 2h} \][/tex]
Therefore, the correct answer is the second option:
[tex]\[ w = \frac{148 - 12h}{12 + 2h} \][/tex]
We start with the given equation:
[tex]\[ 148 = 2(6w + 6h + hw) \][/tex]
First, distribute the 2 on the right-hand side:
[tex]\[ 148 = 12w + 12h + 2hw \][/tex]
We want to solve for [tex]\( w \)[/tex] in terms of [tex]\( h \)[/tex]. To do this, let's isolate [tex]\( w \)[/tex]:
1. Combine like terms on the right-hand side:
[tex]\[ 148 = 12w + 12h + 2hw \][/tex]
2. Move the [tex]\( 12h \)[/tex] term to the left-hand side:
[tex]\[ 148 - 12h = 12w + 2hw \][/tex]
3. Factor [tex]\( w \)[/tex] out of the terms on the right-hand side:
[tex]\[ 148 - 12h = w(12 + 2h) \][/tex]
4. Divide both sides by [tex]\( (12 + 2h) \)[/tex] to isolate [tex]\( w \)[/tex]:
[tex]\[ w = \frac{148 - 12h}{12 + 2h} \][/tex]
Let's compare this to the given equivalent equations:
- [tex]\( w = \frac{148 - 6h}{12 + h} \)[/tex]
- [tex]\( w = \frac{148 - 12h}{12 + 2h} \)[/tex]
- [tex]\( w = 136 - 14h \)[/tex]
- [tex]\( w = 136 - 10h \)[/tex]
Comparing directly, we see that:
[tex]\[ w = \frac{148 - 12h}{12 + 2h} \][/tex]
is exactly equivalent to our derived equation because both the numerator and denominator match.
Thus, the equivalent equation is:
[tex]\[ w = \frac{148 - 12h}{12 + 2h} \][/tex]
So, the correct equation is:
[tex]\[ w = \frac{148 - 12h}{12 + 2h} \][/tex]
Therefore, the correct answer is the second option:
[tex]\[ w = \frac{148 - 12h}{12 + 2h} \][/tex]
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.